Understanding the Economic Impact of Health Care-Associated Infections: A Cost Perspective Analysis. Issue 2 (March 2019) - Scott, R. Douglas; Culler, Steven D.; Rask, Kimberly J.
Abstract : The economic impacts from preventing health care-associated infections (HAIs) can differ for patients, health care providers, third-party payers, and all of society. Previous studies from the provider perspective have estimated an economic burden of approximately 10 billion annually for HAIs. The impact of using a societal cost perspective has been illustrated by modifying a previously published analysis to include the economic value of mortality risk reductions. The resulting costs to society from HAIs exceed 200 billion annually. This article describes an alternative hospital accounting framework outlining the cost of a quality model which can better incorporate the broader societal cost of HAIs into the provider perspective.